PENGARUH PEMBELAJARAN TUTOR SEBAYA TERHADAP HASIL BELAJAR MATEMATIKA KELAS V SEKOLAH DASAR - Anistyani, Tri Ayu, Slameto; Radia, Elvira Hoesein (Jurnal Karya Pendidikan Matematika, 2018)
Abstract:This study aims to know the improvement of learning outcomes of mathematics class V in school which is considered has good learning outcomes but still need to be improved.  The method of this study is Classroom Action Research (CAR) which is conducted in 2 cycles. The research model which is used is peer tutors appropriated with the demands of the 2013 curriculum that is to remember, understand, apply, analyze, evaluate, and create. Besides, it is also adapted to the current educational demands through the 4C strategy namely creativity, critical thinking, collaboration, and communication especially in C3 that is collaboration.  After the research was conducted, there was a change in the cognitive learning outcomes of cycle I that occured after the implementation of the action on the cycle II.  The psychomotor learning outcomes also increased, that was on the observation of students’ cooperation in the peer tutor group which is getting better if viewed in the terms of how the tutor explains, material exploration, etc.  The affective learning outcomes also increased on the students’ behavior. So it can be concluded that peer tutor learning can improve the results of cognitive, affective, and psychomotor learning on mathematics subjects.Keywords:  peer tutor, learning outcomes, cooperation.